Conversion of DAPM Institution Community Empowerment Trust Fund Allocation Transactions in Konda District into Sharia Contracts - Kalsum, Ummi; Mongkito, Abdul Wahid (Institut Agama Islam Negeri Kendari, 2023)
This research aims to convert the Community Empowerment Allocation Fund Distribution Transaction contract into a Sharia-compliant alternative for individuals seeking to avoid usury. It employs a qualitative approach, focusing on a case study of the DAPM Institute in Konda District, Southeast Sulawesi. Data gathered through observation, interviews, and documentation reveals that the transaction contracts in the Women's Savings and Loans (SPP) and Productive Economic Enterprises (UEP) programs in Konda District contain elements of Riba. These programs primarily cater to community needs for goods and services procurement and serve as capital or additional business capital, which can be substituted with murabahah, istishna, mudharabah, and musyarakah contracts. In conclusion, financing for goods and services should utilize murabahah or istisna contracts, while capital or additional business capital may employ mudharabah or musyarakah contracts.